Tire
Patent Information
- Application Number
- CN202511954459.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-18
- Filing Date
- 2025-12-23
- Publication Date
- 2026-10-23
AI Technical Summary
[0018]根据本发明,可以实现轮胎的湿抓地性能和耐磨耗性能的综合性能的进一步提升。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to a tire. Background Technology
[0002] In recent years, various solutions have been proposed to meet the requirements for improving the fuel efficiency, grip, and wear resistance of tires installed on vehicles (for example, patent documents 1-4), but there is still a desire to further improve performance.
[0003] [Existing Technical Documents]
[0004] [Patent Literature]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 2019-218481
[0006] [Patent Document 2] Japanese Patent Application Publication No. 2020-59769
[0007] [Patent Document 3] Japanese Patent Application Publication No. 2021-25006
[0008] [Patent Document 4] Japanese Patent Application Publication No. 2022-121896 Summary of the Invention
[0009] [The problem the invention aims to solve]
[0010] The objective of this invention is to further improve the overall performance of tires in terms of wet grip and wear resistance.
[0011] [Methods used to solve problems]
[0012] This invention relates to a tire.
[0013] It is a tire with a tread section, characterized in that,
[0014] The tread portion uses a rubber composition that, after vulcanization, has a breaking energy E (MPa·%) greater than 11000 MPa·%. The rubber composition comprises, as a rubber component, more than 60 parts by mass of styrene-butadiene rubber (SBR) with a styrene content of less than 25% by mass, and more than 10 parts by mass of isoprene-based rubber, and, relative to 100 parts by mass of the rubber component, more than 105 parts by mass of silica and more than 25 parts by mass of resin component.
[0015] The destructive energy E (MPa·%) was measured by a high-speed tensile test (temperature: 23℃, tensile speed: 10m / s).
[0016] The product of the thickness T (mm) of the tread and the destructive energy E (MPa·%) (T×E) is greater than 65000mm·MPa·%.
[0017] [The effects of the invention]
[0018] According to the present invention, the overall performance of tires in terms of wet grip and wear resistance can be further improved. Detailed Implementation
[0019] [1] Features of the tire of the present invention
[0020] First, the features of the tire of the present invention will be described.
[0021] 1. Summary
[0022] The tire of the present invention is a tire having a tread. The tread is formed using a rubber composition, wherein the rubber composition, as a rubber component, contains more than 60 parts by mass of styrene-butadiene rubber (SBR) with a styrene content of less than 25% by mass per 100 parts by mass of the rubber component, and contains more than 10 parts by mass of isoprene-based rubber. Furthermore, relative to 100 parts by mass of the rubber component, the rubber composition contains more than 105 parts by mass of silica and more than 25 parts by mass of resin component. Moreover, the vulcanized breaking energy E (MPa•%) of the rubber composition for the tread is greater than 11000 MPa•%, the breaking energy E (MPa•%) being measured by a high-speed tensile test (temperature: 23°C, tensile speed: 10 m / s), and the product of the tread thickness T (mm) and the breaking energy E (MPa•%) (T×E) is greater than 65000 mm•MPa•%.
[0023] By incorporating these features, as described below, the overall performance of tires, including wet grip and wear resistance, can be further improved.
[0024] 2. The mechanism of the tire's performance effect according to the present invention
[0025] The mechanism by which the tire of the present invention exhibits the above-mentioned effects can be considered as follows.
[0026] (1) Contains low-styrene SBR
[0027] As described above, the tread portion of the tire of the present invention, as a rubber component, contains styrene-butadiene rubber (SBR) with a styrene content of less than 25% by weight and more than 60 parts by weight of styrene in 100 parts by weight of the rubber component.
[0028] It can be assumed that by forming a tread tread with SBR containing more than 60 parts by mass of styrene per 100 parts by mass, specifically less than 25% by mass of styrene, the increase in tread tread rigidity caused by the styrene domain at low temperatures can be suppressed, and the rubber can be kept soft even at low temperatures. This results in better road surface following and improved wet grip performance.
[0029] Furthermore, by blending a large amount of SBR with a low styrene content, tiny styrene regions can be formed within the rubber matrix, improving the polymer's mobility and allowing the polymer chains to move flexibly. As a result, this can be considered to improve road surface responsiveness and enhance wet grip performance.
[0030] (2) Rubber containing isoprene
[0031] In this invention, in addition to the aforementioned low-styrene SBR, the tread portion also contains more than 10 parts by mass of isoprene-based rubber per 100 parts by mass of the rubber component.
[0032] It can be assumed that, as a result, a phase separation structure is formed between SBR and isoprene-based rubber, resulting in the presence of micro-layers of different hardness within the rubber phase. This makes it easier to increase the energy loss generated when the tread rubber deforms. Furthermore, by incorporating micro-layers of different hardness within the rubber phase, wet grip performance can be improved.
[0033] (3) Contains silicon dioxide
[0034] In the tread portion of the present invention, as a reinforcing filler, it further contains silica in an amount greater than 105 parts by mass relative to 100 parts by mass of the rubber component. It is considered that by containing such a large amount of silica, the heat generation can be further improved because the flexible, small styrene regions easily generate friction with the silica, thereby enhancing the wet grip performance of the tread surface. Furthermore, it is considered that by containing a large amount of silica, the reinforcement of the polymer is improved, thereby enhancing abrasion resistance.
[0035] (4) Contains resin components
[0036] In this invention, the tread surface contains not only silica but also a large amount of resin, specifically more than 25 parts by mass relative to 100 parts by mass of the rubber component. It can be argued that by containing such a large amount of resin, the energy loss of the rubber composition increases, thereby improving wet grip performance.
[0037] (5) Destructive energy
[0038] In this invention, the destructive energy E (MPa·%) of the tread surface is greater than 11000MPa·%, which means that with such a large destructive energy, it is difficult for cracks that lead to wear to occur, thereby improving wear resistance.
[0039] The aforementioned breaking energy E can be determined by performing a high-speed tensile test using the vulcanized rubber composition. Specifically, a No. 7 dumbbell-shaped test piece is prepared from the vulcanized rubber composition, and a high-speed tensile test (temperature: 23°C, tensile speed: 10 m / s) is performed using a high-speed tensile testing machine such as the Shimadzu "HITS-T10" to obtain the breaking strength TB (MPa) and the elongation at break EB (%). Then, based on the obtained breaking strength TB (MPa) and elongation at break EB (%), the breaking energy E is calculated using the following formula.
[0040] E = TB × EB / 2
[0041] (6) Relationship between tread thickness and destructive energy E
[0042] In this invention, the product of the tread thickness T (mm) and the destructive energy E (MPa·%) (T×E) is greater than 65000mm·MPa·%, which means that by using such a large value, the wear resistance performance can be further improved.
[0043] In this invention, it can be considered that by synergistically leveraging the above-mentioned effects, the overall performance of wet grip and abrasion resistance can be further improved.
[0044] [2] A more preferred embodiment of the tire of the present invention
[0045] The tire of the present invention can achieve more significant effects by employing the following methods.
[0046] 1. Low-styrene SBR
[0047] As mentioned above, wet grip performance can be improved by using low-styrene SBR with a styrene content of less than 25% by mass. In this case, it can be considered that as the styrene content decreases, the glass transition temperature (Tg) also decreases further, the breaking energy increases, and the abrasion resistance is further improved. At the same time, wet grip performance can be further improved.
[0048] In this invention, the styrene content of the low-styrene SBR is more preferably 20% by mass or less, further preferably 15% by mass or less, and particularly preferably 10% by mass or less. On the other hand, as a lower limit, it is preferably 3% by mass or more, more preferably 5% by mass or more, and further preferably 7% by mass or more.
[0049] Here, "SBR containing more than 60 parts by mass of styrene and less than 25% by mass in 100 parts by mass of rubber component" means that the amount of SBR in 100 parts by mass of rubber component is more than 60 parts by mass, and the amount of styrene in all SBR is less than 25% by mass.
[0050] That is, when the rubber composition contains one styrene-containing polymer (SBR), it means that the styrene content is 25% by mass or less. When the rubber composition contains multiple styrene-containing polymers (SBR), it means that the styrene content is 25% by mass or less, calculated by the sum of the products of the styrene content (by mass) of each polymer and the amount of that polymer mixed relative to 100 parts by mass of the rubber composition.
[0051] More specifically, if 100 parts by mass of rubber composition contain SBR1 (X1 parts by mass) with a styrene content of S1 mass% and SBR2 (X2 parts by mass) with a styrene content of S2 mass%, the styrene content calculated by the formula {(S1×X1)+(S2×X2)} / (X1+X2) is less than 25 mass%.
[0052] In addition, the amount of styrene contained in the rubber component of the vulcanized rubber composition can be determined and calculated by solid-state nuclear magnetic resonance (solid-state NMR) or Fourier transform infrared spectroscopy (FTIR).
[0053] As described above, the SBR content in 100 parts by weight of the rubber component is greater than 60 parts by weight, more preferably greater than 65 parts by weight, and even more preferably greater than 70 parts by weight. As an upper limit, for example, it is preferably less than 90 parts by weight, more preferably less than 85 parts by weight, and even more preferably less than 80 parts by weight.
[0054] The glass transition temperature (Tg) of each SBR contained in the rubber component is preferably -25°C or less, more preferably -40°C or less, even more preferably -55°C or less, and particularly preferably -70°C or less. On the other hand, as a lower limit, it is preferably -95°C or more, more preferably -90°C or more, even more preferably -85°C or more, and particularly preferably -80°C or more.
[0055] It should be noted that the glass transition temperature (Tg) of the aforementioned SBR can be determined by measuring the temperature distribution curve of tanδ using a viscoelasticity measuring device such as the "EPLEXOR" series manufactured by GABO. Specifically, under the conditions of a frequency of 10 Hz, an initial strain of 10%, an amplitude of ±0.5%, and a heating rate of 2℃ / min, the temperature distribution curve of tanδ is measured, and the temperature corresponding to the largest tanδ value in the range above -100℃ and below 40℃ is taken as the glass transition temperature (Tg).
[0056] It should be noted that when there are two or more points with the largest tanδ value in the range of -100℃ to 40℃, the point with the lowest temperature is taken as the glass transition temperature (Tg). For example, in this invention, when the tanδ peak value is in the range of -100℃ to 40℃, according to the above definition, the peak temperature is taken as the glass transition temperature (Tg). Furthermore, for example, when a temperature distribution curve is obtained where the tanδ peak value exists in the range below -100℃, and tanδ gradually decreases with increasing temperature in the range of -100℃ to 40℃, according to the above definition, the glass transition temperature (Tg) is -100℃.
[0057] 2. Isoprene-based rubber
[0058] As described above, by including more than 10 parts by mass of isoprene-based rubber in 100 parts by mass of the rubber component (excluding low-styrene SBR), and by incorporating micro-layers of varying hardness within the rubber phase, improved wet grip performance and resistance to blockage can be achieved. The content of isoprene-based rubber in 100 parts by mass of the rubber component is more preferably greater than 15 parts by mass, and even more preferably greater than 20 parts by mass. On the other hand, as an upper limit, it is preferably less than 40 parts by mass, and more preferably less than 35 parts by mass.
[0059] Specific isoprene-based rubbers include natural rubber (NR), modified natural rubber (modified NR), modified natural rubber (modified NR), and synthetic polyisoprene (isoprene rubber (IR), modified isoprene rubber (modified IR)), among which NR with excellent strength is preferred. It should be noted that NR can be made from materials commonly used in the tire industry, such as SVR-L, SIR20, RSS#3, and TSR20.
[0060] 3. Silicon dioxide
[0061] As described above, by containing a large amount of silica (more than 105 parts by mass relative to 100 parts by mass of the rubber component), the wet grip performance can be improved. More preferably, it is greater than 120 parts by mass, further preferably greater than 130 parts by mass, and particularly preferably greater than 140 parts by mass. On the other hand, there is no particular upper limit, but it is preferably less than 190 parts by mass, more preferably less than 180 parts by mass, further preferably less than 170 parts by mass, and particularly preferably less than 160 parts by mass.
[0062] 4. Resin
[0063] As described above, by containing a large amount of resin component (more than 25 parts by weight per 100 parts by weight of rubber component), wet grip performance can be improved while ensuring abrasion resistance. More preferably, it is more than 35 parts by weight, further preferably more than 45 parts by weight, and particularly preferably more than 55 parts by weight. As an upper limit, there is no particular limitation, but it is preferably less than 85 parts by weight, more preferably less than 80 parts by weight, further preferably 75 parts by weight, and particularly preferably less than 70 parts by weight.
[0064] Specific resin components include, for example, rosin-based resins, styrene-based resins, coumarone-based resins, terpene-based resins, C5 resins, C9 resins, C5C9 resins, and acrylic resins. Among these, C5 resins and C9 resins are more preferred, and hydrogenated dicyclopentadiene resin (DCPD resin) or AMS resin (α-methylstyrene resin) are particularly preferred. Furthermore, DCPD-C9 resin is also preferred.
[0065] 5. Destructive energy
[0066] As described above, the wear resistance is improved by having a large destructive energy of greater than 11000 MPa·%, and at the same time, wet grip performance is improved. More preferably, it is greater than 13000 MPa·%, and even more preferably, it is greater than 15000 MPa·%. As an upper limit, there is no particular limitation, for example, it is preferably less than 20000 MPa·%, more preferably less than 18000 MPa·%, and even more preferably less than 16000 MPa·%.
[0067] 6. Tread thickness and destructive energy
[0068] As described above, by making the product of the tread thickness T (mm) and the breaking energy E (MPa·%) (T×E) a larger value greater than 65000mm·MPa·%, further improvements in wear resistance and wet grip performance are achieved. More preferably, it is greater than 75000mm·MPa·%, more preferably greater than 85000mm·MPa·%, and even more preferably greater than 95000mm·MPa·%. There is no particular upper limit; for example, it is preferably less than 150000mm·MPa·%, more preferably less than 130000mm·MPa·%, more preferably less than 110000mm·MPa·%, and even more preferably less than 100000mm·MPa·%.
[0069] 7. Relationship between SBR quantity and flatness ratio
[0070] Aspect ratio is the ratio of tire section height to tire section width. It can be considered that the smaller the ratio (low aspect ratio), the larger the contact area with the road surface, thereby improving wet grip performance.
[0071] On the other hand, it can be argued that by including SBR in the tread, the road surface tracking is improved, thereby enhancing wet grip performance.
[0072] That is, it can be achieved by increasing the amount of SBR C in 100 parts by mass of the rubber component. S The product of (parts by mass) and tire aspect ratio A (%) (C) S ×A), which can further improve wet grip performance. Specifically, C S ×A is preferably greater than 2000, more preferably greater than 3500, and even more preferably greater than 5000. As an upper limit, there is no particular limitation; for example, it is preferably less than 6500, more preferably less than 6000, and even more preferably less than 5500.
[0073] 8. Relationship between silica content and negative profile ratio
[0074] Negative profile ratio refers to the ratio (%) of the total open area of multiple grooves to the virtual contact area of the tread surface when all multiple grooves are filled (the total contact area of the tire's entire circumference when the tire with all multiple grooves filled is pressed against a flat surface under normal conditions of normal internal pressure and normal load). It can be considered that the smaller this ratio (low negative profile ratio), the larger the contact area with the road surface becomes, thus generating a large energy loss over the entire tread surface, thereby further improving wet grip performance.
[0075] On the other hand, it can be argued that, as mentioned above, an improvement in wet grip performance can also be achieved by using a large amount of silica, which is used as a filler to enhance the tread area.
[0076] That is, it can be considered that by appropriately controlling the silica content C relative to 100 parts by mass of rubber component, SI Balancing the ratio (parts by weight) with the tire's negative profile ratio N (%) can further improve wet grip performance. Specifically, the ratio (C... SI The ratio ( / N) is preferably greater than 3, more preferably greater than 3.5. There is no particular upper limit, but for example, it is preferably less than 4.5, more preferably less than 4.
[0077] It should be noted that the above negative profile ratio can be obtained from the grounding shape under normal rim, normal internal pressure, and normal load conditions.
[0078] Specifically, the ground contact shape is obtained by assembling a tire onto a standard rim, applying standard internal pressure, allowing it to stand at 25°C for 24 hours, then applying ink to the tire surface, pressing it onto thick paper (camber angle 0°) under standard load, and transferring the print onto the thick paper. The tire is rotated 72° circumferentially each time, and the print is performed at 5 locations. That is, 5 ground contact shapes are obtained. For the 5 ground contact shapes, the average of the maximum length along the tire axial direction is L, and the average of the length perpendicular to the axial direction is W. The negative profile ratio (%) is calculated as [1 - {average area of the 5 ground contact shapes (ink portion) transferred to the thick paper / (L × W)}] × 100 (%). Here, the average length and area are a simple average of the 5 values, where L × W refers to the area of the virtual surface obtained by connecting the blank portions of the main groove and transverse groove when the ground contact shape is obtained.
[0079] Here, "normal condition" means that the tire is assembled on a normal rim and filled with normal internal pressure, and is unloaded.
[0080] It should be noted that "standard rim" refers to the rim specified for each tire within a specification system that includes the tire's base specifications. For example, in JATMA (Japan Automobile Tire Association), it refers to the standard rim with applicable dimensions listed in the "JATMA Yearbook." In ETRTO (European Tyre and Rim Technical Organization), it refers to the "Measuring Rim" listed in the "Standards Manual." In TRA (Tire and Rim Association, Inc.), it refers to the "Design Rim" listed in the "Yearbook." Refer to JATMA, ETRTO, and TRA in that order. If applicable dimensions are available when referring to these specifications, then follow those specifications. Furthermore, in the case of tires not specified in the specifications, it refers to the rim with the smallest diameter and the narrowest width among rims that can be assembled with rims and can maintain internal pressure, that is, rims that will not leak air from between the rim and the tire.
[0081] Secondly, "standard tire pressure" refers to the air pressure specified for each tire within the specification system that includes the tire's base specification. In JATMA, it refers to the "maximum air pressure," in ETRTO it refers to the "inflation pressure," and in TRA it refers to the maximum value recorded in the table "Tire Load Limits at Various Cold Inflation Pressures." References are made in the order of JATMA, ETRTO, and TRA, and if applicable dimensions are available, that specification is used. Furthermore, in the case of tires not specified in the specification, it refers to the standard tire pressure (of which 250 kPa or higher) for other tire sizes (as specified in the specification) recorded with the standard rim as the standard rim. It should be noted that if multiple standard tire pressures of 250 kPa or higher are listed, the minimum value is used.
[0082] Additionally, "normal load" refers to the load specified for each tire in each specification within the specification system that includes the tire's base specification; it is the maximum mass that can be loaded onto the tire. In JATMA, it refers to "maximum load capacity," in ETRTO it refers to "load capacity," and in TRA it refers to the maximum value recorded in the "Tire Load Limits at Various Cold Inflation Pressures" section of the sidewall specification. Similar to "normal rim pressure" and "normal internal pressure," it is referenced in the order of JATMA, ETRTO, and TRA, and if applicable dimensions are available at the time of reference, that specification is followed. Next, in the case of tires not specified in the specification, the normal load W is calculated using the following methods. L .
[0083] V = {(Dt / 2)} 2 -(Dt / 2-Ht) 2}×π×Wt
[0084] W L =0.000011×V+175
[0085] W L Normal load (kg)
[0086] V: Virtual volume of the tire (mm) 3 )
[0087] Dt: Tire outer diameter Dt (mm)
[0088] Ht: Tire section height (mm)
[0089] Wt: Tire cross-sectional width (mm)
[0090] 9. Relationship between resin content and negative profile ratio
[0091] As mentioned above, it can be considered that by appropriately controlling the amount of resin component C relative to 100 parts by mass of rubber component, R Balancing the resin content (parts by weight) and the tire's negative profile ratio N (%) can further improve wet grip performance. Specifically, the resin content C R The ratio of (parts by mass) to negative profile rate N (%) (C) R The ratio ( / N) is preferably greater than 1.5, more preferably greater than 2.0. There is no particular upper limit, but for example, it is preferably less than 3.5, more preferably less than 3.0.
[0092] 10. Thickness and multi-layering of the tread area
[0093] The thickness of the tread is preferably 5 mm or more, more preferably 6 mm or more, and even more preferably 8 mm or more. Regarding the upper limit, it is preferably 20 mm or less, more preferably 18 mm or less, and even more preferably 16 mm or less. This makes the tread more easily deformable due to flexing, improving ground contact and thus further enhancing wet grip performance.
[0094] Furthermore, the tread layer can be formed by a single layer, or by forming two layers with a base rubber layer inside the outermost tread rubber layer; alternatively, it can have three or four or more layers. In this case, the thickness of the tread rubber layer in the entire tread layer is preferably 10% or more. This allows sufficient friction to be generated between the tread surface and the road surface, enabling the transmission of sufficient frictional force to the tire interior, thereby further improving wet grip performance. It should be noted that, considering the friction generated between the tread surface and the road surface, the thickness of the tread rubber layer is more preferably 70% or more.
[0095] The tread rubber layer is not limited to the outermost tread rubber layer formed on the tread surface. If there are two or more layers within 5 mm from the tread surface inward, it is acceptable as long as at least one layer meets the conditions of the rubber composition.
[0096] It should be noted that the tread portion refers to the area that forms the contact patch with the tire, and it is the part located further outward in the radial direction from components containing fibrous materials, such as the carcass, belt ply, and belt reinforcement ply. The thickness of the tread portion can be measured by aligning the bead portion with the standard rim width in a cross-section cut along the radial direction of the tire.
[0097] Furthermore, the tread thickness refers to the thickness of the tread on the equatorial plane of the tire in the radial direction section of the tire. When the tread is formed by a single rubber composition, it is the thickness of that rubber composition; when it is formed by a laminated structure of multiple rubber compositions, it is the total thickness of these layers.
[0098] For example, in the case of a groove on the tire equatorial surface, the thickness refers to the distance from the intersection of the straight line connecting the outermost endpoint of the tire in the radial direction with the tire equatorial surface to the innermost interface of the tread in the radial direction.
[0099] The thickness of the tread can be calculated by adding the thickness of the driving tread rubber layer (the sum of all layers if there are 2 or more layers) and the thickness of the base rubber layer (the sum of all layers if there are 2 or more layers).
[0100] 11. Particle size of silica
[0101] Considering the ease with which friction occurs with the polymer, the particle size (average primary particle size) of silica is preferably 17 nm or less. As a lower limit, for example, it is preferably greater than 8 nm. It can be considered that by using silica with a small particle size, the contact frequency with the polymer (styrene region) can be increased, thereby improving wet grip performance during high-speed driving.
[0102] It should be noted that the average primary particle size is calculated by directly observing the silica extracted from the rubber composition cut from the tire using an electron microscope (TEM) or similar method, and by calculating the equivalent cross-sectional diameter and average value based on the area of each silica particle obtained.
[0103] [3] Implementation
[0104] The present invention will now be described in detail based on its embodiments.
[0105] 1. Rubber composition
[0106] In the tire of the present invention, the rubber composition forming the tread (tread rubber composition) can be obtained by appropriately adjusting the types and quantities of various compounding materials such as the rubber components, fillers, softeners, vulcanizing agents and vulcanization accelerators described below.
[0107] (1) Compounding materials
[0108] (a) Rubber composition
[0109] As mentioned above, low-styrene SBR and isoprene-based rubbers were used as rubber components. Other rubber components that can be used include diene rubbers such as butadiene rubber (BR) and nitrile rubber (NBR), butyl rubbers such as butyl rubber, and thermoplastic elastomers such as styrene-butadiene-styrene block copolymer (SBS) and styrene-butadiene block copolymer (SB), which are commonly used in tire manufacturing.
[0110] (I) SBR
[0111] The weight-average molecular weight of the SBR is, for example, greater than 100,000 and less than 2,000,000. Furthermore, in this invention, as described above, the styrene content in the SBR composition is less than 25% by mass. The vinyl content (1,2-bonded butadiene content) of the SBR is, for example, greater than 5% by mass and less than 70% by mass. It should be noted that the vinyl content of the SBR refers to the 1,2-bonded butadiene content relative to the total butadiene portion within the SBR composition. Additionally, the structural identification of the SBR (determination of styrene content and vinyl content) can be performed, for example, using NMR spectroscopy. 1 H-NMR or 13 The composition is determined by C-NMR. The amounts of components such as "styrene content" and "vinyl content" are correlated with the complex elastic modulus (E). * Unlike physical properties such as total styrene, true values exist that are independent of the measurement method; therefore, it is preferable to use the most accurate measurement method possible. Regarding the total styrene content in the rubber components, the examples in this specification are calculated according to the formulas described herein, but tires can also be analyzed using, for example, Py-GC / MS.
[0112] There are no particular limitations on SBR; for example, emulsion-polymerized styrene-butadiene rubber (E-SBR) and solution-polymerized styrene-butadiene rubber (S-SBR) can be used. SBR can be either unmodified or modified. Alternatively, hydrogenated SBR, obtained by hydrogenating the butadiene portion of SBR, can also be used. Hydrogenated SBR can be obtained by subsequently hydrogenating the BR portion of SBR, or by copolymerizing styrene, ethylene, and butadiene to achieve the same structure.
[0113] As a modified SBR, any SBR having a functional group that interacts with fillers such as silica is acceptable. Examples include end-modified SBRs (end-modified SBRs with the aforementioned functional groups at the end) where at least one end of the SBR is modified with a compound (modifier) having the aforementioned functional groups, main-chain modified SBRs with the aforementioned functional groups on the main chain, main-chain end-modified SBRs with the aforementioned functional groups on both the main chain and the end (e.g., main-chain end-modified SBRs with the aforementioned functional groups on the main chain and at least one end modified by the aforementioned modifier), and end-modified SBRs that introduce hydroxyl or epoxy groups by modification (coupling) with a polyfunctional compound having two or more epoxy groups in the molecule.
[0114] Examples of the aforementioned functional groups include, for example, amino, amide, silyl, alkoxysilyl, isocyanate, imino, imidazo, urea, ether, carbonyl, oxycarbonyl, mercapto, thioether, dithioether, sulfonyl, sulfinyl, thiocarbonyl, ammonium, imide, hydrazine, azo, diazo, carboxyl, nitrile, pyridyl, alkoxy, hydroxyl, oxygen, and epoxy groups. It should be noted that these functional groups may have substituents.
[0115] Alternatively, as a modified SBR, for example, an SBR modified with a compound (modifier) represented by the following formula can be used.
[0116]
Chemistry 1
[0117]
[0118] It should be noted that, in the formula, R 1 R 2 and R 3 They may be the same or different, representing alkyl, alkoxy, silyloxy, acetal, carboxyl (-COOH), mercapto (-SH), or derivatives thereof. R 4 and R 5 They can be the same or different, representing hydrogen atoms or alkyl groups. R 4 and R 5 It can bond and form a ring structure with nitrogen atoms. n represents an integer.
[0119] As a modified SBR modified by the compound (modifier) represented by the above formula, an SBR modified by using the polymerization end (active end) of solution-polymerized styrene-butadiene rubber (S-SBR) with the compound represented by the above formula can be used (modified SBR, etc. as described in Japanese Patent Application Publication No. 2010-111753).
[0120] As R 1 R 2 and R 3Preferably, it is an alkoxy group (preferably an alkoxy group with 1 to 8 carbon atoms, more preferably an alkoxy group with 1 to 4 carbon atoms). As R 4 and R 5 Preferably, it is an alkyl group (preferably an alkyl group having 1 to 3 carbon atoms). n is preferably 1 to 5, more preferably 2 to 4, and even more preferably 3. Additionally, R... 4 and R 5 When bonded together with nitrogen atoms to form a cyclic structure, a 4- to 8-membered ring is preferred. It should be noted that alkoxy groups also include cycloalkoxy groups (such as cyclohexyloxy groups) and aryloxy groups (such as phenoxy and benzyloxy groups).
[0121] Specific examples of the aforementioned modifiers include 2-dimethylaminoethyltrimethoxysilane, 3-dimethylaminopropyltrimethoxysilane, 2-dimethylaminoethyltriethoxysilane, 3-dimethylaminopropyltriethoxysilane, 2-diethylaminoethyltrimethoxysilane, 3-diethylaminopropyltrimethoxysilane, 2-diethylaminoethyltriethoxysilane, and 3-diethylaminopropyltriethoxysilane. These can be used individually or in combination of two or more.
[0122] Additionally, modified SBRs can also be made using compounds (modifiers) such as: polyethylene glycol diglycidyl ether, glycerol triglycidyl ether, trimethylolethane triglycidyl ether, trimethylolpropane triglycidyl ether, etc., polyglycidyl ethers of polyols; polyglycidyl ethers of aromatic compounds having two or more phenolic groups, such as diglycidylated bisphenol A; polyepoxide compounds such as 1,4-diglycidylbenzene, 1,3,5-triglycidylbenzene, and polyepoxide liquid polybutadiene; tertiary amines containing epoxy groups, such as 4,4'-diglycidyl diphenylmethylamine and 4,4'-diglycidyl dibenzylmethylamine; diglycidyl aniline, N,N'-diglycidyl-4-glycidyloxyaniline, and diglycidyl o-toluidine. Tetraglycidyl-m-phenylenediamine, tetraglycidylaminodiphenylmethane, tetraglycidyl-p-phenylenediamine, diglycidylaminomethylcyclohexane, tetraglycidyl-1,3-diaminomethylcyclohexane, and other diglycidylamino compounds; acyl chlorides containing amino groups such as bis(1-methylpropyl)carbamoyl chloride, 4-morpholinocarbonyl chloride, 1-pyrrolidinecarbonyl chloride, N,N-dimethylformyl chloride, and N,N-diethylformyl chloride; silane compounds containing epoxy groups such as 1,3-bis-(glycidyloxypropyl)tetramethyldisiloxane and (3-glycidyloxypropyl)pentamethyldisiloxane; (trimethylsilyl)[3-(trimethoxysilyl)propyl]sulfide, (trimethylsilyl)[ Silane compounds containing thioether groups, such as 3-(triethoxysilyl)propyl] sulfide, (trimethylsilyl)[3-(tripropoxysilyl)propyl] sulfide, (trimethylsilyl)[3-(tributoxysilyl)propyl] sulfide, (trimethylsilyl)[3-(methyldimethoxysilyl)propyl] sulfide, (trimethylsilyl)[3-(methyldiethoxysilyl)propyl] sulfide, (trimethylsilyl)[3-(methyldipropoxysilyl)propyl] sulfide, (trimethylsilyl)[3-(methyldibutoxysilyl)propyl] sulfide, etc.; N-substituted aziridine compounds such as ethyleneimine and acrylamide; methyltriethoxysilane, N,N-bis(trimethylsilyl)-3-aminopropyl Alkoxysilanes such as alkyltrimethoxysilane, N,N-bis(trimethylsilyl)-3-aminopropyltriethoxysilane, N,N-bis(trimethylsilyl)aminoethyltrimethoxysilane, and N,N-bis(trimethylsilyl)aminoethyltriethoxysilane; (thio)benzophenone compounds having amino groups and / or substituted amino groups, such as 4-N,N-dimethylaminobenzophenone, 4-N,N-di-tert-butylaminobenzophenone, 4-N,N-diphenylaminobenzophenone, 4,4'-bis(dimethylamino)benzophenone, 4,4'-bis(diethylamino)benzophenone, and N,N,N',N'-bis-(tetraethylamino)benzophenone.Benzaldehyde compounds containing amino groups and / or substituted amino groups, such as 4-N,N-dimethylaminobenzaldehyde, 4-N,N-diphenylaminobenzaldehyde, and 4-N,N-divinylaminobenzaldehyde; N-substituted pyrrolidones such as N-methyl-2-pyrrolidone, N-vinyl-2-pyrrolidone, N-phenyl-2-pyrrolidone, N-tert-butyl-2-pyrrolidone, and N-methyl-5-methyl-2-pyrrolidone; N-substituted piperidinones such as N-methyl-2-piperidinone, N-vinyl-2-piperidinone, and N-phenyl-2-piperidinone; N-methyl-ε-caprolactam, N-phenyl-ε-caprolactam, N-methyl-ω-laurolactam, N-vinyl-ω-laurolactam, N-methyl-β-propiolactam, and N- N-substituted lactams such as phenyl-β-propiolactam; and N,N-bis(2,3-epoxypropoxy)-aniline, 4,4-methylenebis(N,N-glycidylaniline), tris(2,3-epoxypropyl)-1,3,5-triazine-2,4,6-triones, N,N-diethylacetamide, N-methylmaleimide, N,N-diethylurea, 1,3-dimethylvinylurea, 1,3-divinylvinylurea, 1,3-diethyl-2-imidazolinone, 1-methyl-3-ethyl-2-imidazolinone, 4-N,N-dimethylaminoacetophenone, 4-N,N-diethylaminoacetophenone, 1,3-bis(diphenylamino)-2-propanone, 1,7-bis(methylethylamino)-4-heptanone, etc. It should be noted that modification using the above compounds (modifiers) can be carried out by known methods.
[0123] As an SBR (Self-Borne Blender), for example, SBRs manufactured and sold by companies such as Sumitomo Chemical Co., Ltd., ENEOS Materials Co., Ltd., Asahi Kasei Corporation, and Zeon Corporation of Japan can be used. It should be noted that SBRs can be used alone or in combination of two or more types.
[0124] (II) Isoprene-based rubber
[0125] Examples of isoprene-based rubbers include natural rubber (NR), modified natural rubber (modified NR), modified natural rubber (modified NR), and synthetic polyisoprene (isoprene rubber (IR), modified isoprene rubber (modified IR)). Among these, NR, with its superior strength, is preferred. It should be noted that the isoprene-based rubber content in 100 parts by mass of the rubber component is as described above.
[0126] For specific types of natural rubber (NR), products commonly used in the tire industry, such as SVR-L, SIR20, RSS#3, and TSR20, can be used. For natural rubber (IR), there are no particular limitations, and products commonly used in the tire industry, such as IR2200, can be used. For modified NR, examples include deproteinized natural rubber (DPNR) and high-purity natural rubber (UPNR). For modified NR, examples include epoxidized natural rubber (ENR), hydrogenated natural rubber (HNR), and grafted natural rubber. For modified IR, examples include epoxidized isoprene rubber, hydrogenated isoprene rubber, and grafted isoprene rubber. These can be used individually or in combination of two or more types.
[0127] (III) BR
[0128] In this invention, BR may be further included as needed. In this case, the BR content in 100 parts by weight of the rubber component is preferably 5 parts by weight or more, more preferably 7 parts by weight or more. Alternatively, it is preferably 15 parts by weight or less, more preferably less than 10 parts by weight.
[0129] The weight-average molecular weight of BR is, for example, greater than 100,000 and less than 2,000,000. The vinyl content of BR is, for example, greater than 1% by mass and less than 30% by mass. The cis content of BR is, for example, greater than 1% by mass and less than 98% by mass. The trans content of BR is, for example, greater than 1% by mass and less than 60% by mass.
[0130] There are no particular limitations on the type of BR used; BR with high cis content (cis content above 90%), low cis content, and BR containing syndiotactic polybutadiene crystals can all be used. BR can be either unmodified or modified; examples of modified BR include those incorporating the aforementioned functional groups. These can be used individually or in combination of two or more. It should be noted that the cis content can be determined using infrared absorption spectroscopy.
[0131] As a BR (Brandinger), products from companies such as Ube Industries, Inc., ENEOS Materials Co., Ltd., Asahi Kasei Corporation, and Zeon Corporation can be used.
[0132] (IV) Other rubber components
[0133] In addition, as other rubber components, nitrile rubber (NBR) and other rubbers (polymers) commonly used in tire manufacturing may be included as needed.
[0134] The raw materials (monomers) for the aforementioned SBR, BR, and other synthetic rubbers can be derived from petroleum-based substances or recycled from rubber products such as tires and non-rubber products such as polystyrene.
[0135] The monomer obtained through recycling (recycled monomer) is not particularly limited, and examples include recycled isoprene, recycled butadiene, and recycled aromatic vinyl compounds. Examples of butadiene include 1,2-butadiene and 1,3-butadiene. Examples of aromatic vinyl compounds are not particularly limited, and examples include styrene. Preferably, recycled butadiene and / or recycled styrene are used as raw materials.
[0136] There are no particular limitations on the manufacturing method of the recycled monomer. For example, it can be synthesized from recycled naphtha obtained by decomposing rubber products such as tires. Furthermore, there are no particular limitations on the manufacturing method of the recycled naphtha. For example, rubber products such as tires can be decomposed under high temperature and pressure, microwave decomposition can be used, or extraction can be performed after mechanical crushing.
[0137] Furthermore, the raw materials (monomers) for synthetic rubbers such as SBR and BR can be derived from biomass. There are no particular limitations on the types of monomers derived from biomass, and examples include butadiene and aromatic vinyl compounds derived from biomass. Examples of butadiene include 1,2-butadiene and 1,3-butadiene. Examples of aromatic vinyl compounds are not particularly limited, and examples include styrene. Additionally, there are no particular limitations on the methods for producing biomass monomers; for example, they can be obtained through biological and / or chemical and / or physical transformations of plants and animals. Representative biological transformations include microbial fermentation; examples of chemical and / or physical transformations include catalyst-based transformations, high-temperature transformations, high-pressure transformations, electromagnetic wave transformations, supercritical fluid transformations, and combinations thereof. Biomass sources for these monomers include sugars and wood, plant residues after the extraction of useful components, ethanol from plants, and biomass naphtha.
[0138] The term "biomass polymer" is not particularly limited to polymers synthesized from biomass monomer components. Examples include polybutadiene rubber synthesized from butadiene derived from biomass, and aromatic vinyl / butadiene copolymers synthesized from butadiene derived from biomass and / or aromatic ethylene derived from biomass. Examples of such aromatic vinyl / butadiene copolymers include, for instance, styrene-butadiene rubber synthesized from butadiene derived from biomass and / or styrene derived from biomass.
[0139] Whether the polymer's raw material comes from biomass can be determined by the pMC (percent Modern Carbon) measured based on ASTM D 6866-10.
[0140] pMC refers to the sample 14 C concentration and standard modern carbon (C) reference 14 The ratio of C concentration is an indicator used to represent the biomass ratio of the compound (rubber). The significance of this value is explained below.
[0141] 1 mole of carbon atoms (6.02 × 10⁻⁶) 23 Of these, approximately one trillionth, or about 6.02 × 10⁻⁶, is present. 11 Individual 14 C. 14 Carbon (C) is known as a radioactive isotope with a half-life of 5730 years, decreasing regularly. All of these decays take 226,000 years to completely decompose. Therefore, it can be considered that the carbon dioxide and other substances in the atmosphere, after being fixed by plants and taking more than 226,000 years to form fossil fuels such as coal, oil, and natural gas, initially fixed and contained within these fossil fuels, represent a significant portion of the carbon dioxide that was initially fixed within them. 14 Carbon has completely decayed. Therefore, in the 21st century, fossil fuels such as coal, oil, and natural gas contain absolutely no carbon. 14 Therefore, the chemicals produced from these fossil fuels contain absolutely no carbon (C). 14 C element.
[0142] On the other hand, cosmic rays undergo nuclear reactions in the atmosphere, continuously generating... 14 C, and the consequences of radioactive decay 14 The phase equilibrium of decreasing carbon, in Earth's atmospheric environment, 14 The amount of C is constant. Therefore, as mentioned above, the matter from biomass resources undergoing material cycling in the current environment... 14 The C concentration relative to all C atoms is approximately 1 × 10⁻⁶. -12 The values are approximately mol%. Therefore, the difference between these values can be used to calculate the proportion of compounds derived from natural resources (compounds derived from biomass) in a given compound (rubber) (biomass ratio).
[0143] Should 14 C is typically determined as follows. Accelerator mass spectrometry based on a tandem accelerator is used. 13 C concentration ( 13 C / 12 C) 14 C concentration ( 14 C / 12 C) Determination. In the determination, as... 14 The standard for C concentration in modern carbon is based on the carbon in the natural cycle as of 1950. 14C concentration. As a specific standard substance, the oxalic acid standard provided by NIST (National Institute of Standards and Technology) was used. The radioactivity of carbon in this oxalic acid (carbon content per gram of carbon) was determined. 14 The radioactivity intensity of C is differentiated by each carbon isotope. 13 The C-correction is a fixed value, and the decay-corrected value from 1950 to the date of measurement is used as the standard. 14 The value of C concentration (100%). The ratio of the actual measured value of the sample to this value is the pMC value.
[0144] Therefore, if rubber is made from materials derived from 100% biomass (natural sources), then despite regional differences, it will show a value of approximately 110 pMC (currently, under normal circumstances, it is mostly not 100). On the other hand, for chemicals derived from fossil fuels such as petroleum, when measuring... 14 At C concentration, it shows approximately 0 pMC (e.g., 0.3 pMC). This value corresponds to a biomass ratio of 0% as described above.
[0145] In conclusion, using rubber or other materials with high pMC values, i.e., high biomass ratios, in rubber compositions is preferred from the perspective of being beneficial to environmental protection and enhancing sustainability.
[0146] (b) Compound materials other than rubber components
[0147] (I) Filler
[0148] As mentioned above, the rubber composition contains silica as a reinforcing filler, but in addition to silica, it may also contain carbon black, graphite, calcium carbonate, talc, alumina, clay, aluminum hydroxide, mica, etc.
[0149] (i-1)Silica
[0150] From the perspective of achieving good durability, the BET specific surface area of silica is preferably greater than 140 m². 2 / g, more preferably greater than 160m 2 / g. On the other hand, from the viewpoint of obtaining good rolling resistance at high speeds, a value of less than 300m is preferred. 2 / g, more preferably less than 250m 2 / g, further preferably less than 220m 2 / g. It should be noted that the above BET specific surface area is the N2SA value determined by the BET method according to ASTM D3037-93.
[0151] At this point, the particle size (average primary particle size) of silica, as described above, is preferably 17 nm or less. It should be noted that the silica content relative to 100 parts by mass of the rubber component is as described above.
[0152] Specific examples of silica include dry-process silica (anhydrous silica) and wet-process silica (hydrated silica). Wet-process silica is preferred due to its higher silanol group content. Additionally, silica made from materials such as aqueous glass or biomass materials such as rice husks can also be used.
[0153] As silicon dioxide, products from companies such as Evonik Industries, Rhodia, Tosoh Silicon Chemicals, Solvay Japan, and Tokuyama Corporation can be used.
[0154] There are no particular limitations on the raw materials used for silica. For example, raw materials derived from minerals such as quartz, raw materials derived from organisms such as rice husks (e.g., silica made from biomass materials such as rice husks), and silica recovered from silica-containing products can also be used. Among these, hydrated silica prepared by a wet process is preferred due to the high prevalence of silanol groups.
[0155] As a biomass material, silica can be obtained by extracting silicates from rice husk ash obtained by burning rice husks using sodium hydroxide solution. The silicates are then reacted with sulfuric acid in the same way as existing wet silica. The resulting silica precipitate is then filtered, washed, dried, and pulverized.
[0156] Silica recovered from products containing silica can be, for example, silica recovered from products containing silica such as electronic components like semiconductors, tires, desiccants, and filter materials such as diatomaceous earth. Furthermore, the method of recovery is not particularly limited, and examples include thermal decomposition and electromagnetic wave decomposition. Of these, silica recovered from electronic components like semiconductors or tires is preferred.
[0157] If silica crystallizes, it becomes insoluble in water, making it impossible to utilize its silicic acid component. By managing the combustion temperature and time, the crystallization of silica in rice husk ash can be suppressed (see Japanese Patent Application Publication No. 2009-2594, Akita Prefectural University Online Journal B, 2019, vol.6, pp.216-222, etc.).
[0158] Amorphous silica extracted from rice husks can be commercially available from companies such as Wilmar.
[0159] It should be noted that these silicas can be used alone or in combination with two or more types. Furthermore, from the perspective of environmental protection and sustainability, the use of biomass silica and recycled silica is preferred.
[0160] (i-2) Silane coupling agent
[0161] When using the above-mentioned silica, it is preferable to include a silane coupling agent together with the silica.
[0162] As a silane coupling agent, there are no particular limitations; examples include bis(3-triethoxysilylpropyl)tetrasulfide, bis(2-triethoxysilylethyl)tetrasulfide, bis(4-triethoxysilylbutyl)tetrasulfide, bis(3-trimethoxysilylpropyl)tetrasulfide, bis(2-trimethoxysilylethyl)tetrasulfide, bis(2-triethoxysilylethyl)trisulfide, and bis(4-trimethoxysilylbutyl)tetrasulfide. bis(3-triethoxysilylpropyl) disulfide, bis(2-triethoxysilylethyl) disulfide, bis(4-triethoxysilylbutyl) disulfide, bis(3-trimethoxysilylpropyl) disulfide, bis(2-trimethoxysilylethyl) disulfide, bis(4-trimethoxysilylbutyl) disulfide, bis(3-trimethoxysilylpropyl) disulfide, bis(2-trimethoxysilylethyl) disulfide, bis(4-trimethoxysilylbutyl) disulfide, 3-trimethoxysilylpropyl-N,N-dimethylsulfide Sulfide systems include thiocarbamoyl tetrasulfide, 2-triethoxysilylethyl-N,N-dimethylthiocarbamoyl tetrasulfide, and 3-triethoxysilylmethylpropyl acrylate monosulfide; thiol systems include 3-mercaptopropyltrimethoxysilane, 2-mercaptoethyltriethoxysilane, and NXT and NXT-Z manufactured by Momentive; vinyl systems include vinyltriethoxysilane and vinyltrimethoxysilane; amino systems include 3-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane; glycidoxy systems include γ-glycidoxypropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane; nitro systems include 3-nitropropyltrimethoxysilane and 3-nitropropyltriethoxysilane; and chlorine systems include 3-chloropropyltrimethoxysilane and 3-chloropropyltriethoxysilane. These can be used alone or in combination with two or more.
[0163] As silane coupling agents, products from companies such as Evonik Industries, Momentive, Shin-Etsu Silicones, Tokyo Chemical Industries, Azmax, and DuPont Toray Specialty Materials can be used.
[0164] The content of silane coupling agent is, for example, greater than 3 parts by mass and less than 25 parts by mass relative to 100 parts by mass of silicon dioxide.
[0165] (ii) Carbon black
[0166] From the viewpoint of improving wet grip by enhancing rigidity and responsiveness, carbon black is preferably included as a reinforcing filler in addition to silica.
[0167] The specific content of carbon black relative to 100 parts by mass of the rubber component is preferably 2 parts by mass or more, more preferably 4 parts by mass or more. On the other hand, it is preferably 15 parts by mass or less, more preferably 12 parts by mass or less.
[0168] There are no particular limitations on carbon black. Examples include furnace black (furnace black) such as SAF, ISAF, HAF, MAF, FEF, SRF, GPF, APF, FF, CF, SCF, and ECF; acetylene black; thermal cracking black (thermal cracking black) such as FT and MT; and channel black (channel black) such as EPC, MPC, and CC. One of these can be used alone, or two or more can be used in combination.
[0169] The preferred CTAB specific surface area (cetyltrimethylammonium bromide) of carbon black is 130 m². 2 / g or more, more preferably 160m 2 / g or more, further preferably 170m 2 / g or more. On the other hand, 250m is preferred. 2 / g or less, more preferably 200m 2 / g or less. It should be noted that the CTAB specific surface area is a value determined according to ASTM D3765-92.
[0170] There are no specific limitations on the specific type of carbon black used; examples include N134, N110, N220, N234, N219, N339, N330, N326, N351, N550, and N762. Commercially available products include those from Asahi Carbon Co., Ltd., Cabot Japan Co., Ltd., Tokai Carbon Co., Ltd., Mitsubishi Chemical Co., Ltd., Lion Corporation, Shin Nippon Chemical Carbon Co., Ltd., and Columbia Carbon Co., Ltd. These can be used individually or in combination of two or more types.
[0171] (iii) Other fillers
[0172] In addition to silica and carbon black, the rubber composition may, as needed, contain fillers commonly used in the tire industry, such as graphite, calcium carbonate, talc, alumina, clay, aluminum hydroxide, and mica. The content of these fillers relative to 100 parts by weight of the rubber component is, for example, greater than 0.1 parts by weight and less than 200 parts by weight.
[0173] (II) Plasticizer components
[0174] To ensure proper dispersion of powdered materials during mixing, it is preferable to use plasticizer components in the rubber composition as needed. It should be noted that plasticizer components here refer to additives such as processing oils or rubber components, liquid rubber, and resin components, which plasticize the rubber composition.
[0175] These plasticizer components can be derived from petroleum, biomass, or naphtha recycled from rubber or non-rubber products. Alternatively, low-molecular-weight hydrocarbon components obtained through the thermal cracking and extraction of used tires or products containing various components can be used as plasticizers. Among these, plasticizer components derived from biomass or recycled materials are preferred as sustainable plasticizer components.
[0176] It should be noted that the aforementioned plasticizer components can be used alone or in combination with two or more. In this case, the content of the plasticizer component relative to 100 parts by weight of the rubber component is preferably 20 parts by weight or more, more preferably 30 parts by weight or more, and even more preferably 40 parts by weight or more. As an upper limit, for example, it is preferably 100 parts by weight or less, more preferably 80 parts by weight or less, and even more preferably 60 parts by weight or less.
[0177] It should be noted that the content of plasticizer components also includes the amount of oil contained in rubber (oil-extended rubber), etc.
[0178] (i) Oil
[0179] Examples of oils include, for example, mineral oils (usually referring to processing oils), vegetable oils, or mixtures thereof. Examples of mineral oils (processing oils) include paraffinic processing oils, aromatic processing oils, and cycloalkane processing oils. Examples of vegetable oils include castor oil, cottonseed oil, linseed oil, rapeseed oil, soybean oil, palm oil, coconut oil, peanut oil, rosin, pine oil, pine tar, tall oil, corn oil, rice bran oil, safflower oil, sesame oil, olive oil, sunflower seed oil, palm kernel oil, camellia oil, jojoba oil, macadamia nut oil, and tung oil. These can be used alone or in combination of two or more. Additionally, from a life cycle assessment perspective, waste oil or waste cooking oil used as lubricant in rubber mixing mills or automotive engines can also be appropriately utilized.
[0180] As specific processing oils (mineral oils), products from companies such as Idemitsu Kosan Co., Ltd., Sankyo Oil & Chemical Co., Ltd., ENEOS Co., Ltd., OLISOY Co., Ltd., H&R Co., Ltd., Toyokuni Oil Co., Ltd., Showa Shell Oil Co., Ltd., Fuji Kosan Co., Ltd., etc. can be used.
[0181] (ii) Liquid rubber
[0182] Liquid rubber, as an example of a plasticizer component, refers to polymers that are liquid at room temperature (25°C) and are rubber components that can be extracted from vulcanized tires using acetone. Examples of liquid rubber include farnesene polymers, liquid diene polymers, and their hydrides.
[0183] Farnesene polymers refer to polymers obtained by polymerizing farnesenes and possessing structural units based on farnesenes. Farnesenes exist as isomers such as α-farnesene ((3E,7E)-3,7,11-trimethyl-1,3,6,10-dodecathetene) and β-farnesene (7,11-dimethyl-3-methylene-1,6,10-dodecathetene).
[0184] Farnesene polymers can be homopolymers of farnesene (farnesene homopolymers) or copolymers of farnesene and vinyl monomers (farnesene-vinyl monomer copolymers).
[0185] Examples of liquid diene polymers include liquid styrene-butadiene copolymer (liquid SBR), liquid butadiene polymer (liquid BR), liquid isoprene polymer (liquid IR), and liquid styrene-isoprene copolymer (liquid SIR).
[0186] The weight-average molecular weight (Mw) of polystyrene converted by gel permeation chromatography (GPC) of liquid diene polymers, for example, is greater than 1.0 × 10⁻⁶. 3 Less than 2.0×10 5 It should be noted that, in this specification, the Mw of the liquid diene polymer is a polystyrene conversion value determined by gel permeation chromatography (GPC).
[0187] The content of liquid rubber (the total content of liquid farnesene polymers, liquid diene polymers, etc.) is, for example, greater than 1 part by mass and less than 100 parts by mass relative to 100 parts by mass of rubber component.
[0188] As a liquid rubber, products from companies such as Kuraray Corporation and Clayville Corporation can be used.
[0189] (iii) Resin composition
[0190] The resin component also functions as an adhesive agent. It can be solid or liquid at room temperature. Specific resin components include, for example, rosin-based resins, styrene-based resins, coumarone-based resins, terpene-based resins, C5 resins, C9 resins, C5C9 resins, and acrylic resins. Among these, C5 and C9 resins are preferred. Examples of such resins include dicyclopentadiene resin (DCPD resin) and AMS resin (α-methylstyrene resin). It should be noted that two or more types can be used together. Furthermore, these resin components can be modified with groups that can react with silica, etc., as needed. It should be noted that the content of the resin component relative to 100 parts by weight of the rubber component is as described above.
[0191] Rosin-based resins are resins obtained by processing rosin, with rosin acid as the main component. These rosin-based resins (rosin derivatives) can be classified according to whether they have been modified or not, into unmodified rosin and modified rosin derivatives. Examples of unmodified rosin include tall oil rosin, resin rosin, wood rosin, disproportionated rosin, polymerized rosin, hydrogenated rosin, and rosin with other chemical modifications. Modified rosin derivatives are modifications of unmodified rosin, including rosin esters, unsaturated carboxylic acid-modified rosin derivatives, unsaturated carboxylic acid-modified rosin esters, rosin amide compounds, and rosin amine salts.
[0192] Styrene-based resins are polymers that use styrene-based monomers as structural monomers. Examples include polymers polymerized with styrene-based monomers as the main component (50% by mass or more). Specifically, in addition to homopolymers obtained by homopolymerization of styrene-based monomers (styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, α-methylstyrene, p-methoxystyrene, p-tert-butylstyrene, p-phenylstyrene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, etc.), copolymers obtained by copolymerization of two or more styrene-based monomers, copolymers of styrene-based monomers with other monomers that can be copolymerized with them can also be listed.
[0193] Examples of other monomers include acrylonitriles such as acrylonitrile and methacrylonitrile; unsaturated carboxylic acids such as acrylic acid and methacrylic acid; unsaturated carboxylic acid esters such as methyl acrylate and methyl methacrylate; dienes such as chloroprene, butadiene, and isoprene; alkenes such as 1-butene and 1-pentene; and α,β-unsaturated carboxylic acids or their anhydrides such as maleic anhydride.
[0194] Among coumarone-based resins, coumarone-indene resin is preferred. Coumarin-indene resin is a resin containing coumarone and indene as monomeric components constituting the resin backbone (main chain). Other monomeric components in the backbone besides coumarone and indene include styrene, α-methylstyrene, methylindene, and vinyltoluene.
[0195] The content of coumarin indole resin is, for example, greater than 1.0 part by weight and less than 50.0 parts by weight per 100 parts by weight of rubber component.
[0196] The hydroxyl value (OH value) of coumarin indole resin is, for example, greater than 15 mg KOH / g and less than 150 mg KOH / g. It should be noted that the OH value refers to the amount of potassium hydroxide, expressed in milligrams, required to neutralize the acetic acid bonded to the hydroxyl group when 1 g of resin is acetylated, and is a value determined by potentiometric titration (JIS K 0070:1992).
[0197] The softening point of coumarin indene resin is, for example, greater than 30°C and less than 160°C. Furthermore, the softening point is the temperature at which the ball drops when measured using a ring and ball softening point tester as specified in JIS K 6220-1:2001.
[0198] Examples of terpene-based resins include polyterpenes, terpene phenols, and aromatic modified terpene resins. Polyterpenes are resins obtained by polymerizing terpene compounds and their hydrides. Terpene compounds are composed of (C5H8) resins. n The composition of hydrocarbons and their oxygen-containing derivatives is represented by the form of monoterpenes (C14-C24-C24). 10 H 16 ), sesquiterpenes (C 15 H 24 ), diterpenes (C 20 H 32 Compounds with terpenes as their basic skeleton, such as α-pinene, β-pinene, dipentene, limonene, myrcene, allocirrhene, ocimene, α-phellandrene, α-terpinene, γ-terpinene, terpinene oil, 1,8-cineole, 1,4-cineole, α-terpineol, β-terpineol, γ-terpineol, etc.
[0199] As polyterpenes, in addition to terpene resins such as α-pinene resin, β-pinene resin, limonene resin, dipentene resin, and β-pinene / limonene resin, which are made from the aforementioned terpene compounds, hydrogenated terpene resins that have undergone hydrogenation treatment can also be listed. As terpene phenols, resins copolymerized with the aforementioned terpene compounds and phenolic compounds, as well as resins that have undergone hydrogenation treatment, can be listed. Specifically, resins formed by condensing the aforementioned terpene compounds, phenolic compounds, and formaldehyde can be listed. It should be noted that phenolic compounds include, for example, phenol, bisphenol A, cresol, and xylenol. As aromatic modified terpene resins, resins obtained by modifying terpene resins with aromatic compounds, as well as resins that have undergone hydrogenation treatment, can be listed. It should be noted that, as aromatic compounds, there are no particular limitations as long as they have an aromatic ring. Examples include phenols such as phenol, alkylphenols, alkoxyphenols, and phenols containing unsaturated hydrocarbon groups; naphthols such as naphthols, alkylnaphthols, alkoxynaphthols, and naphthols containing unsaturated hydrocarbon groups; styrene derivatives such as styrene, alkylstyrene, alkoxystyrene, and styrene containing unsaturated hydrocarbon groups; coumarone, indene, etc.
[0200] "C5 resin" refers to resin obtained by polymerizing C5 fractions. Examples of C5 fractions include petroleum fractions with 4 to 5 carbon atoms, such as cyclopentadiene, pentene, pentadiene, and isoprene. Dicyclopentadiene resin (DCPD resin) is a suitable C5-based petroleum resin.
[0201] "C9 resin" refers to resins obtained by polymerizing C9 fractions, or products obtained by hydrogenation or modification of these fractions. Examples of C9 fractions include petroleum fractions with 8 to 10 carbon atoms, such as vinyltoluene, alkylstyrene, indene, and methylindene. Specific examples include coumarone-indene resin, coumarone resin, indene resin, and aromatic vinyl resins. For aromatic vinyl resins, based on economic efficiency, ease of processing, and good exothermic properties, homopolymers of α-methylstyrene (AMS resin) or styrene, or copolymers of α-methylstyrene and styrene, are preferred, with copolymers of α-methylstyrene and styrene being more preferred. Commercially available products from companies such as KRATON and Eastman Chemical can be used as aromatic vinyl resins.
[0202] "C5C9 resin" refers to a resin obtained by copolymerizing the aforementioned C5 fraction and C9 fraction, or it can be a product obtained by hydrogenation or modification of these fractions. Examples of C5 and C9 fractions include the aforementioned petroleum fractions. Commercially available products from companies such as Tosoh Corporation and Luhua Corporation can be used as C5C9 resin.
[0203] There are no particular limitations on the acrylic resin; for example, solvent-free acrylic resins can be used.
[0204] Solvent-free acrylic resins include (meth)acrylic resins (polymers) synthesized via high-temperature continuous polymerization (high-temperature continuous bulk polymerization) with minimal use of polymerization initiators, chain transfer agents, organic solvents, etc., as excipients (as described in US Patent 4,414,370, Japanese Patent Application Publication No. 59-6207, Japanese Patent Publication No. 5-58005, Japanese Patent Application Publication No. 1-313522, US Patent 5,010,166, and the Toa Synthetic Research Yearbook TREND2000 No. 3, pp. 42-45). It should be noted that in this invention, (meth)acrylic acid refers to both methacrylic acid and acrylic acid.
[0205] As monomeric components constituting the above-mentioned acrylic resins, examples include (meth)acrylic acid, (meth)acrylates (alkyl esters, aryl esters, aralkyl esters, etc.), (meth)acrylamide, and (meth)acrylamide derivatives, etc.
[0206] In addition, as a monomer component constituting the above-mentioned acrylic resin, aromatic vinyl compounds such as styrene, α-methylstyrene, vinyltoluene, vinylnaphthalene, divinylbenzene, trivinylbenzene, and divinylnaphthalene can be used together with (meth)acrylic acid or (meth)acrylic acid derivatives.
[0207] The aforementioned acrylic resins can be resins composed solely of (meth)acrylic acid, or resins that incorporate components other than (meth)acrylic acid as constituent elements. Furthermore, the aforementioned acrylic resins may contain hydroxyl, carboxyl, or silanol groups, etc.
[0208] As a resin component, products from companies such as Maruzen Petrochemical Co., Ltd., Sumitomo Bakelite Co., Ltd., Yasuhara Chemical Co., Ltd., Tosoh Co., Ltd., Rutgers Chemicals Co., Ltd., BASF Corporation, Arizona Chemical Co., Ltd., Nippon Paint Co., Ltd., Nippon Shokubai Co., Ltd., ENEOS Co., Ltd., Arakawa Chemical Industry Co., Ltd., Taoka Chemical Industry Co., Ltd., etc. can be used.
[0209] (III) Stearic acid
[0210] The rubber composition preferably includes stearic acid. The content of stearic acid, relative to 100 parts by weight of the rubber component, is, for example, greater than 0.5 parts by weight and less than 10.0 parts by weight. As stearic acid, conventionally known stearic acid can be used, for example, products from Nippon Yusen Co., Ltd., NOF Corporation, Kao Corporation, Fujifilm, Kojun Pharmaceutical Co., Ltd., Chiba Fatty Acid Co., Ltd., etc.
[0211] (IV) Anti-aging agents
[0212] The rubber composition preferably contains an antioxidant. The content of the antioxidant is, for example, greater than 0.5 parts by weight and less than 10 parts by weight, more preferably 1 part by weight or more, relative to 100 parts by weight of the rubber component.
[0213] As an antioxidant, there are no particular limitations, but examples include naphthylamine antioxidants such as phenyl-α-naphthylamine; diphenylamine antioxidants such as octyl diphenylamine and 4,4'-bis(α,α'-dimethylbenzyl)diphenylamine; p-phenylenediamine antioxidants such as N-isopropyl-N'-phenyl-p-phenylenediamine, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, and N,N'-di-2-naphthyl-p-phenylenediamine; quinoline antioxidants such as polymers of 2,2,4-trimethyl-1,2-dihydroquinoline; monophenol antioxidants such as 2,6-di-tert-butyl-4-methylphenol and styrylated phenol; and bisphenol, triphenol, and polyphenol antioxidants such as tetra-[methylene-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate]methane. These can be used individually or in combination of two or more.
[0214] It should be noted that, as an anti-aging agent, products from companies such as Seiko Chemical Co., Ltd., Sumitomo Chemical Co., Ltd., Ouchi Shinsei Chemical Co., Ltd., and Flexsys can be used.
[0215] (V) wax
[0216] The rubber composition preferably contains wax. The wax content is, for example, 0.5 to 20 parts by weight, preferably 1.0 to 15 parts by weight, and more preferably 1.5 to 10 parts by weight, relative to 100 parts by weight of the rubber component.
[0217] As for waxes, there are no particular limitations. Examples include petroleum-based waxes such as paraffin wax and microcrystalline wax; natural waxes such as plant-based waxes and animal-based waxes; and synthetic waxes made from polymers such as ethylene and propylene. They can be used alone or in combination of two or more.
[0218] It should be noted that, for example, products from companies such as Ouchi Shinshin Chemical Industry Co., Ltd., Nippon Seiwa Co., Ltd., and Seiko Chemical Co., Ltd. can be used as waxes.
[0219] (VI) Zinc oxide
[0220] The rubber composition may contain zinc oxide. The zinc oxide content, relative to 100 parts by weight of the rubber component, is, for example, greater than 0.5 parts by weight and less than 10 parts by weight. As the zinc oxide, conventionally known zinc oxides may be used, such as products from Mitsui Metal Mining Co., Ltd., Toho Zinc Industry Co., Ltd., Hakusui Technology Co., Ltd., Seido Chemical Industry Co., Ltd., Sakai Chemical Industry Co., Ltd., etc.
[0221] (VII) Crosslinking agents and vulcanization accelerators
[0222] The rubber composition preferably contains a crosslinking agent such as sulfur. The content of the crosslinking agent is, for example, greater than 0.1 parts by weight and less than 10.0 parts by weight per 100 parts by weight of the rubber component.
[0223] Examples of sulfur compounds commonly used in the rubber industry include powdered sulfur, settled sulfur, colloidal sulfur, insoluble sulfur, highly dispersed sulfur, and soluble sulfur. These can be used individually or in combination of two or more.
[0224] It should be noted that, for example, products from companies such as Tsurumi Chemical Industry Co., Ltd., Karuizawa Sulfur Co., Ltd., Shikoku Chemical Industry Co., Ltd., Flexsys Co., Ltd., Nippon Kanryu Kogyo Co., Ltd., and Hosoi Chemical Industry Co., Ltd. can be used as sulfur.
[0225] As crosslinking agents other than sulfur, specific examples include sulfur-containing vulcanizing agents such as Tackirol V200 manufactured by Taoka Chemical Industry Co., Ltd., KA9188 (1,6-bis(N,N'-dibenzylthiocarbamoyl dithio)hexane) manufactured by Lanxess, and organic peroxides such as dicumyl peroxide.
[0226] The rubber composition preferably contains a vulcanization accelerator. The content of the vulcanization accelerator is, for example, greater than 0.3 parts by weight and less than 10.0 parts by weight per 100 parts by weight of the rubber component.
[0227] Examples of vulcanization accelerators include thiazole-based vulcanization accelerators such as 2-mercaptobenzothiazole, di-2-benzothiazole disulfide, and N-cyclohexyl-2-benzothiazole sulfenamide; thiuram-based vulcanization accelerators such as tetramethylthiuram disulfide (TMTD), tetrabenzylthiuram disulfide (TBzTD), and tetra(2-ethylhexyl)thiuram disulfide (TOT-N); sulfenamide-based vulcanization accelerators such as N-cyclohexyl-2-benzothiazole sulfenamide, N-tert-butyl-2-benzothiazole sulfenamide, N-oxodiethylene-2-benzothiazole sulfenamide, and N,N'-diisopropyl-2-benzothiazole sulfenamide; and guanidine-based vulcanization accelerators such as diphenylguanidine, di-o-tolylguanidine, and o-tolylbiguanidine. These can be used alone or in combination of two or more.
[0228] (VIII) Other
[0229] In addition to the components mentioned above, the rubber composition may also contain additives commonly used in the tire industry, such as fatty acid metal salts, carboxylic acid metal salts, organic peroxides, and anti-reversion (vulcanization reversion) agents, as needed. The content of these additives relative to 100 parts by weight of the rubber component is, for example, greater than 0.1 parts by weight and less than 200 parts by weight.
[0230] (2) Preparation of rubber composition
[0231] The tread rubber composition can be manufactured by appropriately adjusting the various compounding materials mentioned above and by conventional methods, such as a basic mixing process that includes mixing the rubber components with fillers such as silica and carbon black, and a final mixing process that includes mixing the mixture obtained in the basic mixing process with a crosslinking agent.
[0232] Mixing can be carried out using well-known (closed) mixing machines such as Banbury internal mixers, kneaders, and open mills.
[0233] The mixing temperature in the basic mixing process is, for example, greater than 50°C and less than 200°C, and the mixing time is, for example, greater than 30 seconds and less than 30 minutes. In addition to the above-mentioned components, compounding agents used in the rubber industry can be added as needed in the basic mixing process, such as softeners like oils, stearic acid, zinc oxide, antioxidants, waxes, vulcanization accelerators, etc.
[0234] In the final mixing process, the compound obtained in the basic mixing process is mixed with a crosslinking agent. The mixing temperature in the final mixing process is, for example, above room temperature and below 80°C, and the mixing time is, for example, above 1 minute and below 15 minutes. In addition to the above-mentioned components, vulcanization accelerators, zinc oxide, etc., may be added as needed during the final mixing process.
[0235] 2. Tire manufacturing
[0236] In this embodiment, the tire can be made by molding the rubber composition obtained above into a tread rubber of a specified shape, and then molding it together with other rubber parts on a tire forming machine using conventional methods, thereby producing an uncured tire.
[0237] Specifically, an inner liner (as a component to ensure tire air tightness), a tire carcass (as a component to withstand the load, impact, and air pressure borne by the tire), and a belt layer component (as a component to strongly fasten the tire carcass and improve the rigidity of the tread) are wound on a forming drum. Bead portions (as components to fix the two ends of the tire carcass and fix the tire to the rim) are arranged on both sides of the edge. After being formed into a ring shape, the tread is attached to the center of the outer periphery and the tire sidewall is attached to the radially outer side to form the tire sidewall, thereby producing an uncured tire.
[0238] It should be noted that when the tread layer is designed to form a multi-layer structure with the base rubber layer, the aforementioned rubber components and compounding materials can be used essentially, with appropriate adjustments to their mixing amounts. The rubber composition forming the base rubber layer is obtained through similar kneading. Then, the tread rubber, together with the tread rubber layer, is extruded into a predetermined shape and, along with other tire components, formed on a tire forming machine using conventional methods, thereby producing an uncured tire.
[0239] The uncured tires are then heated and pressurized in a vulcanizing machine to obtain tires. The vulcanization process can be carried out using known vulcanization methods. For example, the vulcanization temperature is greater than 120°C and less than 200°C, and the vulcanization time is greater than 5 minutes and less than 15 minutes.
[0240] As described above, the resulting tire, due to the appropriate control of the ratio of the rubber composition for the tread, the relationship between the thickness of the tread and the breaking energy, etc., can achieve a synergistic effect of various effects, thus further improving wet grip performance.
[0241] Furthermore, the tires of the present invention are not particularly limited in category and can be used as tires for passenger cars, large passenger cars, large SUVs, trucks / buses, two-wheeled vehicles, racing tires, studless anti-skid tires (winter tires), all-season tires, run-flat tires, aircraft tires, mining tires, non-pneumatic tires, etc., and are preferably used as tires for passenger cars.
[0242]
Example
[0243] The following are examples (embodiments) that are considered preferred in practice, but the scope of the invention is not limited to these examples.
[0244] Tires consisting of treads and other rubber components formed by various compound materials as shown below were studied. The results of wet grip performance calculated according to the evaluation method described later are shown in the lower half of Tables 1-3.
[0245] 1. Manufacturing of rubber compositions for tire treads
[0246] Rubber compositions for tire treads are prepared using the various compounding materials shown below.
[0247] (1) Compounding materials
[0248] (a) Rubber composition
[0249] (I) NR: TSR-20
[0250] (II) SBR-1: Modified S-SBR manufactured based on Manufacturing Example 1 described below (styrene content: 25% by mass, vinyl content: 25% by mol), Tg: -50℃, Mw: 750,000.
[0251] (III) SBR-2: Modified S-SBR manufactured based on Manufacturing Example 2 described below (styrene content: 20% by mass, vinyl content: 20% by mol), Tg: -60℃, Mw: 650,000.
[0252] (IV) SBR-3: Modified S-SBR manufactured based on Manufacturing Example 2 described below (styrene content: 10% by mass, vinyl content: 20% by mole, Tg: -25°C, Mw: 600,000).
[0253] (V) SBR-4: Modified S-SBR manufactured based on Manufacturing Example 2 described below (styrene content: 40% by mass, vinyl content: 25% by mole, Tg: -35°C, Mw: 1.2 million).
[0254] (VI) BR: Ube Industries, Inc.'s UBEPOL BR150B (high cis BR) (cis content 97% by mass, trans content 2% by mass, vinyl content 1% by mass)
[0255] (Manufacturing Example 1: Manufacturing of SBR-1)
[0256] The SBR-1 described above was prepared according to the following steps. First, cyclohexane, tetrahydrofuran, styrene, and 1,3-butadiene were added to a nitrogen-purged autoclave reactor. After adjusting the temperature of the reactor contents, n-butyllithium was added to initiate polymerization. Polymerization was then carried out under adiabatic conditions. At the point where the polymerization conversion reached 99%, 1,3-butadiene was added, and polymerization continued for another 5 minutes. N,N-bis(trimethylsilyl)-3-aminopropyltrimethoxysilane was then added as a modifier to initiate the reaction. After the polymerization reaction was completed, 2,6-di-tert-butyl-p-cresol was added, and the solvent was removed by steam stripping. The product was then dried using hot rollers to obtain SBR-1.
[0257] (Manufacturing Example 2: Manufacturing of SBR-2 to SBR-4)
[0258] The SBR-2 to SBR-4 were prepared in the same manner as in Manufacturing Example 1, except that the amount of styrene, vinyl content, and Tg were changed as targets, and 3-dimethylaminopropyltriethoxysilane was used as a modifier.
[0259] (b) Compound materials other than rubber components
[0260] (I) Silica-1: ULTRASIL VN3 (N2SA: 175m) manufactured by Evonik Industries, Inc. 2 / g, average particle size: 17nm)
[0261] (II) Silica-2: ULTRASIL 9100Gr manufactured by Evonik Industries (N2SA: 235m) 2 / g, average particle size: 15nm)
[0262] (III) Silane coupling agent-1: Si266 (bis(3-triethoxysilylpropyl) disulfide) manufactured by Evonik Industries
[0263] (IV) Silane Coupling Agent-2: NXT (3-octanoylthiopropyltriethoxysilane) manufactured by Momentive.
[0264] (V) Carbon black: DIABLACK N220 (N2SA: 115m) manufactured by Mitsubishi Chemical Corporation 2 / g)
[0265] (VI) Resin composition-1: Syltraxx 4401 (α-methylstyrene resin) manufactured by Arizona Chemical Company
[0266] (VII) Resin Component-2: Oppera PR-383 manufactured by ExxonMobil (hydrogenated DCPD resin, aromaticity: 9.6% by mass, softening point: 103℃, Mw: 770)
[0267] (VIII) Oil: Vivatec 500 (aromatic processing oil: TDAE oil) manufactured by H&R Corporation
[0268] (IX) Zinc oxide: Zinc oxide No. 2 manufactured by Mitsui Metals & Minerals Co., Ltd.
[0269] (X) Anti-aging agent: Antigen 6C (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine) manufactured by Sumitomo Chemical Co., Ltd.
[0270] (XI) Stearic acid: Beaded stearic acid "Camellia" manufactured by Nippon Oil Company.
[0271] (XⅡ) Wax: OZOACE 0355 manufactured by Nippon Seiwa Co., Ltd.
[0272] (XⅢ) Sulfur: Powdered sulfur (containing 5% oil) manufactured by Tsurumi Chemical Industry Co., Ltd.
[0273] (XIV) Vulcanization accelerator: Nocceler CZ (N-cyclohexyl-2-benzothiazolyl sulfinamide (CBS)) manufactured by Ouchi Shinshin Chemical Industry Co., Ltd.
[0274] (2) Preparation of rubber composition for tire tread
[0275] According to the formulas shown in Tables 1-3, the materials, except for sulfur and vulcanization accelerator, were mixed at 150°C for 5 minutes using a 1.7-liter Banbury internal mixer manufactured by Kobe Steel Co., Ltd. to obtain the mixture.
[0276] Then, sulfur and vulcanization accelerator are added to the mixture, and it is mixed for 5 minutes at 80°C using an open mill to obtain the rubber compositions for each tire tread.
[0277] 2. Manufacturing of pneumatic tires
[0278] (1) Tread Formation
[0279] Then, using the rubber composition obtained above, the tire tread is formed into a specified shape according to the thicknesses (mm) shown in Tables 1 to 3.
[0280] Then, it is bonded together with other tire components to form an uncured tire, and then vulcanized under pressure at 170°C for 10 minutes to manufacture the test tires of Examples 1 to 12 and Comparative Examples 1 to 5 shown in Tables 1 to 3 (tire size: 195 / 65R15, aspect ratio: 65%, negative profile ratio: 40%, tread thickness: 6mm).
[0281] 3. Parameters
[0282] Then, the No. 7 dumbbell-shaped test pieces, cut and prepared from each test tire, were subjected to high-speed tensile testing (temperature: 23°C, tensile speed: 10 m / s) using a Shimadzu HITS-T10 high-speed tensile testing machine, to obtain the breaking strength TB (MPa) and elongation at break EB (%). Based on the obtained breaking strength TB (MPa) and elongation at break EB (%), the breaking energy E was calculated according to the following formula.
[0283] E = TB × EB / 2
[0284] Then, calculate the tread thickness multiplied by the destructive energy.
[0285] 4. Performance evaluation test
[0286] (1) Evaluation of wet grip performance
[0287] The test tires were installed on all wheels of the vehicle and inflated with air to an internal pressure of 250 kPa. The vehicle was then driven at 100 km / h on a wet test track, and the braking distance was measured.
[0288] Then, using the result of Comparative Example 5 as 100, the result was exponentialized based on the following formula to evaluate wet grip performance. A larger value indicates a shorter braking distance and better wet grip performance.
[0289] wet grip performance
[0290] = [(Results of Comparative Example 5) / (Results of the Test Tires)] × 100
[0291] (2) Evaluation of wear resistance
[0292] All test tires were installed on all wheels of a Japanese-made front-wheel-drive vehicle (2000cc engine), and inflated to an internal pressure of 250 kPa. The tread groove depth was measured before driving. The vehicle was then driven 10,000 km on the test route. After the test, the tread groove depth was measured again. Based on the tread groove depths measured before and after driving, the tread wear was calculated, and the distance traveled corresponding to a 1 mm reduction in tread depth was determined.
[0293] The wear resistance performance was evaluated by taking the result calculated in Comparative Example 5 as 100 and exponentializing it according to the following formula. The larger the value, the longer the driving distance for a 1mm reduction in groove depth (less wear), indicating excellent wear resistance.
[0294] Abrasion resistance = [(Results of the test tire) / (Results of Comparative Example 5)] × 100
[0295] Table 1
[0296]
[0297] Table 2
[0298]
[0299] Table 3
[0300]
[0301] The present invention has been described above based on the embodiments, but the present invention is not limited to the embodiments described above. Various modifications can be made to the embodiments described above within the same or equivalent scope as the present invention.
[0302] This invention (1) is a tire,
[0303] It is a tire with a tread section, characterized in that,
[0304] The tread portion uses a rubber composition to form a vulcanized breakdown energy E (MPa·%) greater than 11000 MPa·%. The rubber composition, as a rubber component, contains more than 60 parts by mass of styrene-butadiene rubber (SBR) with a styrene content of less than 25% by mass per 100 parts by mass, and more than 10 parts by mass of isoprene-based rubber. Furthermore, relative to 100 parts by mass of the rubber component, it contains more than 105 parts by mass of silica and more than 25 parts by mass of resin component.
[0305] The destructive energy E (MPa·%) was measured by a high-speed tensile test (temperature: 23℃, tensile speed: 10m / s).
[0306] The product of the thickness T (mm) of the tread and the destructive energy E (MPa·%) (T×E) is greater than 65000mm·MPa·%.
[0307] The present invention (2) is a tire according to the present invention (1), characterized in that the destructive energy (MPa·%) is greater than 13000MPa·%.
[0308] The present invention (3) is a tire according to the present invention (2), characterized in that the destructive energy (MPa·%) is greater than 15000MPa·%.
[0309] The present invention (4) is a tire of any combination of any one of the present inventions (1) to (3), characterized in that the product of the thickness (mm) of the tread and the destructive energy (MPa·%) is greater than 75000mm·MPa·.
[0310] The present invention (5) is a tire according to the present invention (4), characterized in that the product of the thickness (mm) of the tread and the destructive energy E (MPa·%) is greater than 95000mm·MPa·%.
[0311] The present invention (6) is a tire of any combination of any one of the present invention (1) to (5), characterized in that the styrene content of the styrene-butadiene rubber (SBR) in the rubber component is less than 20% by mass.
[0312] The present invention (7) is a tire of any combination of any one of the present invention (1) to (6), characterized in that the styrene content of the styrene-butadiene rubber (SBR) in the rubber component is less than 15% by mass.
[0313] The present invention (8) is a tire of any combination of any one of the present invention (1) to (7), characterized in that the content of isoprene rubber in 100 parts by mass of the rubber component is greater than 20 parts by mass.
[0314] The present invention (9) is a tire of any combination of any one of the present inventions (1) to (8), characterized in that the content of silica in the rubber composition is greater than 120 parts by mass relative to 100 parts by mass of rubber component.
[0315] The present invention (10) is a tire of any combination of any one of the present invention (1) to (9), characterized in that the content of resin component in the rubber composition is greater than 45 parts by mass relative to 100 parts by mass of rubber component.
[0316] The present invention (11) is a tire according to the present invention (10), characterized in that, relative to 100 parts by weight of rubber component, the content of resin component in the rubber composition is greater than 55 parts by weight.
[0317] The present invention (12) is a tire of any combination of any one of the present invention (1) to (11), characterized in that the resin component is dicyclopentadiene resin or α-methylstyrene resin.
[0318] The present invention (13) is a tire of any combination of any one of the present inventions (1) to (12), characterized in that the product of the SBR content (parts by mass) in 100 parts by mass of the rubber component and the aspect ratio (%) of the tire is greater than 2000.
[0319] The present invention (14) is a tire of any combination of any one of the present inventions (1) to (13), characterized in that the ratio of the content (parts by mass) of the silica relative to 100 parts by mass of the rubber component to the negative profile ratio (%) of the tread surface is greater than 3.
[0320] The present invention (15) is a tire of any combination of any one of the present inventions (1) to (14), characterized in that the ratio of the content (parts by mass) of the resin component relative to 100 parts by mass of the rubber component to the negative profile ratio (%) of the tread surface is greater than 1.5.
Claims
1. A tire having a tread pattern, Its features are, The tread portion uses a rubber composition that, after vulcanization, has a breaking energy E greater than 11000 MPa·%. The rubber composition, as a rubber component, contains more than 60 parts by mass of styrene-butadiene rubber (SBR) with a styrene content of less than 25% by mass per 100 parts by mass of the rubber component, and more than 10 parts by mass of isoprene-based rubber. Furthermore, relative to 100 parts by mass of the rubber component, the rubber composition contains more than 105 parts by mass of silica and more than 25 parts by mass of resin component. The destructive energy E was measured by a high-speed tensile test, wherein the high-speed tensile temperature was 23℃ and the tensile speed was 10m / s. The product of the tread thickness T and the destructive energy E, T×E, is greater than 65000 mm·MPa·%, where the unit of thickness T is mm and the unit of destructive energy E is MPa·%.
2. The tire according to claim 1, characterized in that, The destructive energy is greater than 13000 MPa.
3. The tire according to claim 2, characterized in that, The destructive energy is greater than 15000 MPa.
4. The tire according to any one of claims 1 to 3, characterized in that, The product of the tread thickness and the destructive energy is greater than 75000 mm·MPa·%, where the thickness is in mm and the destructive energy is in MPa·%.
5. The tire according to claim 4, characterized in that, The product of the tread thickness and the destructive energy is greater than 95000 mm·MPa·%, where the thickness is in mm and the destructive energy is in MPa·%.
6. The tire according to any one of claims 1 to 3, characterized in that, The styrene content of the styrene-butadiene rubber (SBR) in the rubber composition is less than 20% by mass.
7. The tire according to claim 6, characterized in that, The styrene content of the styrene-butadiene rubber (SBR) in the rubber composition is less than 15% by mass.
8. The tire according to any one of claims 1 to 3, characterized in that, The content of isoprene-based rubber in 100 parts by mass of the rubber component is greater than 20 parts by mass.
9. The tire according to any one of claims 1 to 3, characterized in that, The content of silica in the rubber composition is greater than 120 parts by weight relative to 100 parts by weight of the rubber component.
10. The tire according to any one of claims 1 to 3, characterized in that, The content of resin component in the rubber composition is greater than 45 parts by weight relative to 100 parts by weight of rubber component.
11. The tire according to claim 10, characterized in that, The content of resin component in the rubber composition is greater than 55 parts by weight relative to 100 parts by weight of rubber component.
12. The tire according to any one of claims 1 to 3, characterized in that, The resin component is dicyclopentadiene resin or α-methylstyrene resin.
13. The tire according to any one of claims 1 to 3, characterized in that, The product of the SBR content in 100 parts by mass of the rubber component and the tire aspect ratio is greater than 2000. The unit for the SBR quantity is parts by mass, and the unit for the flatness ratio is ( ).
14. The tire according to any one of claims 1 to 3, characterized in that, The ratio of the silica content relative to 100 parts by weight of the rubber component to the negative profile ratio of the tread surface is greater than 3. The unit for the silica content is parts by mass, and the unit for the negative profile ratio is ( ).
15. The tire according to any one of claims 1 to 3, characterized in that, The ratio of the resin content relative to 100 parts by weight of the rubber component to the negative profile ratio of the tread surface is greater than 1.
5. The content of the resin component is expressed in parts by mass, and the negative profile ratio is expressed in parts by mass.
16. The tire according to any one of claims 1 to 3, characterized in that, The thickness of the tread portion is between 5mm and 20mm.
17. The tire according to any one of claims 1 to 3, characterized in that, The content of styrene-butadiene rubber (SBR) in 100 parts by weight of the rubber component is less than 90 parts by weight. The styrene content of the styrene-butadiene rubber (SBR) is 3% by mass or more.
18. The tire according to any one of claims 1 to 3, characterized in that, The content of isoprene-based rubber in 100 parts by mass of the rubber component is less than 40 parts by mass.
19. The tire according to any one of claims 1 to 3, characterized in that, The content of silica in the rubber composition is less than 190 parts by mass relative to 100 parts by mass of the rubber component.
20. The tire according to any one of claims 1 to 3, characterized in that, The content of resin component in the rubber composition is less than 85 parts by weight relative to 100 parts by weight of rubber component.
Citation Information
Patent Citations
Bulk polymerization and polymer
JP1984006207A
Catalytic lumpy production of cyclic ester modified acrylic polymer
JP1989313522A
Bulk polymerization for manufacturing high solid content homogeneous copolymer
JP1993058005B2
Small combustion furnace for manufacturing rice husk ash
JP2009002594A
Rubber composition and tire
JP2010111753A